FDG-PET nodal staging does not correlate with histopathological nodal stage for oesophageal cancers. (August 2015) - Devadas, M.; Mittal, A.; Lin, M.; Cosman, P.; Ziazaris, W.; Wilson, R.; Das, A.; Merrett, N.
Abstract: Objective: To investigate whether pre-operative N-stage (nodal stage) based on FDG-PET for oesophageal cancers, correlates with final histopathology. Additionally, we assessed if N-stage differs for squamous cell cancers compared with adenocarcinomas and if neoadjuvant therapy alters these results. Background: Our current understanding of oesophageal cancer biology means that personalisation of multimodality therapy is based on accurate clinical staging, allied with patient co morbidities and patient preference. Methods: We conducted a retrospective review of consecutive oesophagectomy cases performed over a ten year period (between 2002 and 2013) from a single tertiary centre. A total of 161 patients were identified in the study period. Results: Overall, 103 specimens with 1402 lymph nodes were included. For both Adenocarcinomas (AC) and Squamous Cell Carcinomas (SCC), there was no significant difference between the N-stage determined by CT vs. FDG-PET (p > 0.05). For AC, there was statistically significant under-reporting of the N-stage by PET compared with the final histopathology (p < 0.01). Subgroup analysis showed that neoadjuvant therapy vs. adjuvant therapy alone did not alter the bias for under-reporting of the N-stage for adenocarcinoma by PET-CT (Bland-Altman bias 0.76 vs. bias 0.75). Conclusion: There is little doubt that PET-CT provides useful information in determining metastatic disease however its use in evaluating nodal burden is limited. Theoretically, this should not preclude patients from receiving definitive surgical management but the decision regarding neoadjuvant treatment based on locoregional disease may be affected. Highlights: FDG-PET significantly understages Adenocarcinomas (AC) of the oesophagus when compared with histopathological examination. This is not affected by neoadjuvant therapy. For both Adenocarcinomas (AC) and Squamous Cell Carcinomas (SCC), there was no significant difference between the N-stage determined by CT vs. FDG-PET. FDG-PET provides useful information regarding distant metastatic disease however management algorithms involving neoadjuvant therapy for locoregional disease may be affected.